THE EFFECT OF DRAGON FRUIT PEEL EXTRACTS IN DRINKING WATER THE INTERNAL ORGANS OF THE SUPERIOR VILLAGE CHICKEN FOR BALIBANGTAN (KUB) - I K. A., Juniawan,; Puspani, E.; Warmadewi, D. A. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
In order to replace the excessive use of AGP in Balitbangtan village chickens (KUB), natural feed additives are needed as a substitute for AGP.  This study was to observe the impact of adding dragon fruit (Hylocereus polrhizus) skin to drinking water on the internal organs of KUB chickens. This study was held at Udayana University, Sesetan Lab, Faculty of Animal Husbandry. The assessment lasted up to 8 weeks, using RAL which included four actions and four repetitions. The actions include P0 (without giving dragon fruit peel extract), P1 (giving 3% dragon fruit peel extract), P2 (giving 6% dragon fruit peel extract) and P4 (giving 9% dragon fruit peel extract). Variables were observed in the form of weight percentages of internal organs (liver, heart, spleen, bile and pancreas). The information obtained will be analyzed using variance, if there are significant differences, then carry out Duncan's test. The results from the study of administering 3%, 6% and 9% dragon fruit peel extract in drinking water were not significantly proportional (P>0.05) to the percentage of heart, liver, bile, spleen and pancreas. Through the results of the study, it was concluded that the use of 3%, 6% & 9% dragon fruit peel extract did not affect the internal organs of 8 week old KUB chickens.